REKAYASA ARSITEKTUR JARINGAN INTERNET MENGGUNAKAN FRAMEWORK AGILE KANBAN DAN ANALISIS QoS (Quality of Service) PADA METODE LOAD BALANCING - Abdul Kharis; Darsanto; Mukhsin (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
During the 2022-2023 period, the number of internet users reached 215.63 million people,an increase of 2.67% from the previous year (210.03 million users). However, problems arise due tothe inability of bandwidth capacity to handle traffic loads, resulting in network overload. To overcomethis, it is necessary to have 2 uplinks that are managed using load balancing and failover techniquesto even out the traffic load and maintain connectivity. This study examines the Per ConnectionClassifier (PCC) load balancing technique and Routing with Failover, using the ETSI TIPHONstandard to measure efficiency and stability through parameters such as Throughput, Packet Loss,Delay, and Jitter. In network design using the Agile Kanban framework, starting from designing thetopology to comparing results. The experimental results show that PCC load balancing has betterefficiency and stability than Routing with Failover which refers to the ETSI TIPHON rules. Theresults of the PCC load balancing test on the throughput parameter are 3353.15 Kbps, the packet lossparameter is 8.91%, the delay parameter is 2.2 ms, the jitter parameter is 2.1 ms. Even though thedifference in the test results was not significant, PCC load balancing proved to be the most efficientand stable method for dealing with overloads. The use of the Agile Kanban method in designinginternet networks and implementing load balancing is effective in dealing with overload problems.Keywords: Agile Kanban, Load Balancing, QoS, Failover